Writing Myself Home: A phenomenological enquiry (Existential Analysis: Journal of the Society for Existential Analysis, 2025)
'Home' and unheimlichkeit are phenomena that invite exploration of the complexity of human existence. Through a phenomenological enquiry into my own relationship with home, I explore the potential for finding a new home in meeting with clients in the therapy space.
Keywords: Home; unheimlichkeit; existential migration